Improving Environmental Protection in Nigeria: A Reassessment of the Role of Informal Institutions - Enabulele, Osamuyimen; Ekhator, Eghosa O. (Journal of Sustainable Development Law and Policy, 2025)
The success of an approach or strategy for the implementation of legal instruments in one country does not imply that the same approach or strategy would be successful when replicated in another country because there is no ‘one-size-fits-all approach’ to policy implementation. The rationale for the above assertion is that institutions play a major role in the success of any policy. Undoubtedly, institutional approach provides a solid foundation to explore the interplay between formulation of policies and their effective implementation. Therefore, for an environmental policy to be successfully implemented, the institutional peculiarity of the country must be considered. This article explores the role of informal institutions (embedded institutions) in policy implementation focusing on Sub-Saharan Africa with specific focus on Nigeria. It provides theoretical basis for an informal institutional approach in environmental policy implementation. This article suggests that the institutional approach can be extended to environmental protection and management through informal institutions.